A Comparative Study of Impact of KVKs Managed by Different Agencies in Uttar Pradesh - Narendra Prasad , S. K. Verma , K. M. Singh , L. B. Singh and R. P. Sahu (Indian Journal of Extension Education, 2014)
The Krishi Vigyan Kendra (KVK) provides a strong training support for bringing about production breakthrough inagriculture. Krishi Vigyan Kendras are functional in carrying out extension activities in accordance with governmentprogramme schedule and providing support to raise the skill of the farmers which will help them to increase their farmproductivity. On the basis of findings and observations of the study, it may be concluded that most of the farmers werehaving either marginal or small holdings. Majority of the respondents were having farming as their main occupation. TheKVK beneficiaries differed significantly in case of knowledge, attitude and skill. New agricultural technologiesdissemination through KVK were adopted by the farmers to a considerable extent. Highest adoption was found by theKVK of NGO which may be due to better and adequate infrastructure and other facilities. Among the three selectedKVKs, the performance of KVK of the NGO, Sultanpur was found to be superior. Nearly 60 per cent beneficiariesreported that after receiving training from KVK, their farm productivity increased. Forty per cent of the beneficiaries fullyadopted recommendations of the KVK, while 40 per cent adopted it partially.